Hubungan Pemakaian Kontrasepsi Implant Dengan Gangguan Haid di Puskesmas Sebangar Riau Tahun 2023 - Afrida Yelni (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2023)
Contraception is an effort to prevent pregnancy. It can be temporary, it can be permanent. Contraceptive use is one of the variables that affect fertility (Wikjosastro, 2012). This study is a descriptive study to see the relationship between the use of contraceptive implants and menstrual disorders at the Sebangar Riau Health Center in 2023. The population in this study is women of childbearing age who use implantable birth control at the Sebangar Riau Health Center in 2023, which is 265 people with a sample of 72 people. The results of the study showed. There is a relationship between the use of birth control implants with menstrual disorders with a chi squre test value of 0.002. It is hoped that health agencies can provide more counseling to implant birth control users so as not to worry if menstrual disorders occur because they are not dangerous.